Development and Validation of a Novel Prognostic Model for Acute Myeloid Leukemia Based on Immune-Related Genes - Li, Ran; Ding, Zuoyou; Jin, Peng; Wu, Shishuang; Jiang, Ge; Xiang, Rufang; Wang, Wenfang; Jin, Zhen; Li, Xiaoyang; Xue, Kai; Wu, Xiaolu; Li, Junmin (Frontiers in Immunology, 2021)
Immune response changes in acute myeloid leukemia (AML) are closely related to its prognosis. Further exploration of the pathobiology of AML with a focus on the function of immune-related genes (IRGs) would allow the development of more advanced evaluation and treatment strategies. Here, we established a novel immune-17 signature based on transcriptome data from the TCGA and GTEx databases. We identified immune biology processes and transcriptional dysregulations as critical factors in the development of AML through enrichment analyses. Using LASSO (Least Absolute Shrinkage and Selection Operator) regression analysis, we formulated a prognostic model to predict the overall survival (OS) of AML patients. Incorporation of the immune-17 signature further improved the prognostic accuracy of the ELN2017 risk stratification system. Overall, the immune-17 signature represents a novel useful model for evaluating AML survival outcomes, and may be implemented to contribute to the prolonged OS in these patients by the optimized selection of individualized targeted therapy.